Team, Front cover, Editorial information, Table of Content, Back Cover - Journal Editor (Journal of Tropical Pharmacy and Chemistry, 2013)
J. Trop. Pharm. Chem. 2013. Volume 2 Nomor 3. Team, Front cover, Editorial information, Table of Content, Back Cover